Respon Tanaman Melon (Cucumis melo L.) terhadap Komposisi Media Tanam dan Konsentrasi Pupuk Organik Cair - Dewi Puspa Arisandi; Ferry Santoso; Desi Rejeki; Nur Halimah; Luqi Khoiriyah Latif (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2025)
Good practices of melon cultivation can be done by applying Liquid Organic Fertilizer (POC) and arranging the appropriate composition of the planting media. This study aims to determine the effect composition planting media, concentration of liquid organic fertilizer (POC), and combination of both treatments on the growth and production of melon fruit. The study was arranged using a basic pattern of Completely Randomized Design (CRD) factorial consisting of 2 factors. The first factor is the planting media (M) which consists of 4 levels, namely M0 = soil: rice husks: sand (1: 0: 0); M1 = soil: rice husks: sand (0: 1: 1); M2 = soil: rice husks: sand (1: 0: 1); and M3 = soil: rice husks: sand (1: 1: 1). The second factor is concentration of POC (K) which consists of 3 levels, namely K0 (0%), K1 (5%), and K2 (10%). There are 12 treatment combinatio ns with 3 replications. The results show that combination of treatment of the composition of the planting media in the form of soil: rice husks: sand (0: 1: 1); with a concentration of 10% POC gave the highest results in plant height parameters in the vegetative phase (53.35 cm); plant height in the generative phase (223.51 cm); and melon fruit weight (1132.44 g). The concentration of 10% POC supported the fastest melon flowering (24.92 HST). The composition of planting media consisting of soil: rice husks: sand (0: 1: 1) produced melon plants with the longest roots (61.42 cm).